Are nurses more likely to report providing care plans for chronic disease patients than doctors? Findings from a New Zealand study. (September 2015) - Doolan-Noble, Fiona; Gauld, Robin; Waters, Debra L
Objectives: The main aim of this study was to compare the perceptions of general practitioners (GPs) and primary care nurses (PCNs) in the Southern Region of New Zealand regarding their provision of chronic illness care. Whether PCNs rated their frequency of providing aspects of chronic illness care higher than GPs was a key question. Methods: The modified version of the Patient Assessment of Chronic Illness Care (PACIC) was used to compare the perceptions of GPs and PCNs. Results: Surveys were received from 77% of practices in the Southern region. Responding PCNs were more likely than their GP counterparts to document they provided aspects of chronic illness care 'most of the time' or 'always' in 18 activities from the six M-PACIC domains. Their level of providing patients with formal care plans was surprisingly low. Conclusion: This level of engagement of PCNs with chronic illness care was no surprise. The low number reporting they provided patients with a care plan, most of the time or always, was unexpected. Aspects of care planning, however, were reported as taking place more frequently. This discrepancy between the process of care planning and the outcome, a care plan, is not unique to this region of New Zealand and warrants further research.